Effect Mno3 Nanoparticles On Structural, Optical, And Electrical Properties Of PVP: CMC Blend Films (Journal of the College of Basic Education, 2024)
This Study Demonstrates The Potential Of Mno3 Nanoparticle Addition To Enhance The Properties Of Polymeric Blends, The Effect Of Adding Mno3 Nps Was Studied In A Polymeric Blend Composed Of Polyvinylpyrrolidone (PVP): Carboxymethylcellulose (CMC) With Different Concentrations Of Mno3 Nps (3%, 5%, And 7%), And The Study Of Structural, Optical, And Electrical Properties, The Results Show The Energy Gap Of The (PVA: CMC) Film Was Reduced From 4.48 (Ev) To 3.89 (Ev) By Incorporating 7% Mno3 Nps , This Change Suggests Enhanced Optical Properties, Including Increased Light Transmission And Reflection. Furthermore, The Conductivity Of The Blend Was Increased, Rendering It Suitable For Various Applications Such As, Sensor And Optoelectronics Devices.